Hadroh music as a means of religious communication - Anang Masduki; Prayudha Prayudha; Panqiang Niu; Wajiran Wajiran (International Journal of Visual and Performing Arts, 2024)
This study investigates the role of Islamic art, specifically Hadroh, in conveying religious messages within communities with limited exposure to spiritual practices and religious studies. Given the prevalence of such circumstances, particularly among individuals from lower socioeconomic backgrounds, alternative approaches to religious communication are essential. In response, the Santri Besek of Surokarsan village, Yogyakarta, have adopted Hadroh art as a means of religious preaching. Through a comprehensive examination conducted in Surokarsan village, utilizing methodologies including in-depth interviews, observations, and documentation, this research explores the effectiveness of using art as a medium for religious communication. The findings reveal significant enhancements in da'wah efficacy, particularly among mothers, teenagers, and children. Participants demonstrated heightened enthusiasm towards fostering mosque prosperity, indicative of the impact of art-based religious communication. Notably, the study identifies a notable shift in the religious practices of mothers, with increased engagement in rhythmic recitations of Sholawat accompanied by Hadroh, even among those previously less active in spiritual activities. Furthermore, children exhibit greater receptivity to religious education when delivered through rhythmic or melodic formats, suggesting the potential for innovative approaches to religious instruction. In conclusion, this research underscores the value of incorporating art, particularly Hadroh, in religious communication strategies, particularly within communities facing limited exposure to traditional spiritual practices. By leveraging artistic mediums, such as music and rhythm, this study contributes to a deeper understanding of how to effectively convey religious messages and promote religious engagement among diverse populations.